Development of a Realistic Mathematics Teaching Module on Arithmetic Sequences and Series to Support the Mathematical Literacy of Vocational High School Students - Indira Runturambi; Rosiah J. Pulukadang; Navel Oktaviandy Mangelep; Philoteus E. A. Tuerah; Sylvia J. A. Sumarauw (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The persistently low mathematical literacy of Indonesian students, repeatedly documented in international assessments, is rooted in procedural and decontextualised teaching practices, including in the topic of arithmetic sequences and series at vocational high schools (SMK). This study aimed to produce a realistic mathematics teaching module on arithmetic sequences and series that is valid, practical, and effective for supporting the mathematical literacy of grade X students. A Research and Development approach using Plomp's model was employed, comprising three phases: preliminary research, development/prototyping, and assessment. The subjects were 22 grade X students of SMK Negeri 1 Amurang; three expert validators assessed validity and eight students assessed practicality in a small-group evaluation. Instruments comprised validation sheets, student response questionnaires, and a mathematical literacy test based on the formulating, employing, and interpreting indicators. The results showed that the module met the highly valid criterion (86%), the practical criterion (81.8%), and the effective criterion with a mean N-Gain of 0.84 (high category) and 86.36% classical completeness. The mean test score increased from 17.73 in the pretest to 86.45 in the posttest. These findings confirm that a Realistic Mathematics Education-based module designed through layered formative evaluation can bridge mathematical concepts with students' vocational contexts while strengthening mathematical literacy. This study contributes to the provision of contextual teaching materials for vocational education and opens opportunities for experimentally designed effectiveness testing in further research.